Design a test circuit using altium designer - Ng, Shun Qiang. (2013)
The process of planning and designing of a Printed Circuit Board (PCB) used in testing an IC chip with a footprint of DIP 40, designed by a PhD student, is presented in this report. Firstly, the IC chip is being studied in this project and its features, such as the voltage requirements and the number of inputs and outputs, were outlined in this report. An alternate testing unit was also chosen and discussed.